Impact of miniaturisation on solder joint reliability. (16th July 2008) - Erinc, Muge; Schreurs, Piet J.G.; Geers, Marc G.D.
The ongoing miniaturisation trend in the microelectronics industry enforces component sizes to get smaller, and possibly their geometrical shapes to change. In this study, the thermomechanical fatigue life of lead-free solder joints is investigated with respect to solder size and geometry. In ball grid array packages the pitch size is correlated to the solder ball diameter and the stand-off height. In this study, pitch size is also correlated to the contact angle between the solder and the substrate. Finite element models are constructed for various contact angles with different stand-off heights. Bump/pad interfaces and the bulk solder are analysed by determining plastic strain accumulation and equivalent Von Mises stresses resulting from thermal loading. Geometrical and microstructural criticalities are quantified by describing a geometry factor and a microstructure factor. The geometry factor is related to the shape of the solder, and the microstructure factor is related to the grain boundary area and the mismatch of local crystallographic orientations at the grain boundaries. The influence of these two factors on solder reliability is discussed.